Iodine values of adipose tissue varied among breeds of pigs and were correlated with pork quality. (2nd October 2017) - Testroet, Eric D.; Yoder, Chad L.; Testroet, Amber; Reynolds, Carmen; O'Neil, Mathew R.; Lei, Soi Meng; Beitz, Donald C.; Baas, Tom J.
ABSTRACT: Our objectives were to investigate fatty acid composition variation amongst adipose tissue sites, breed effects on fat quality, and the relationship of pork fat quality to fresh pork quality. Barrows and gilts (n = 347) of five purebred and one commercial crossbred line were fed commercial swine diets with DDGS inclusion at 30% (as fed) from 31.8 kg body weight until 30-d prior to harvest at 111.4 kg. Immediately after harvest, hot carcass weight was determined, adipose tissue was collected from the back, belly, and jowl, and meat samples were taken from the longissimus muscle for evaluation of pork quality. Iodine values (IV) varied between anatomical site and breed. Jowl fat IV were correlated to back and belly fat IV. Minor but significant correlations were observed between IV and meat quality characteristics. These results support our hypotheses that minor relationships exist between fat and fresh pork quality and that IV vary by anatomical location.